Integration of a hybrid laboratory for learning in digital electronics: an educational experience (LACCEI, 2024)
This article describes an educational experience in which a hybrid laboratory consisting of two modalities, remote and hands-on laboratory, was used in a digital electronics course focused on learning a hardware description language. A case study is presented which describes the interaction of students with the hybrid laboratory over a period of 10 weeks, including the number of experiments performed, laboratory reports submitted, and days and hours of access to the remote laboratory. In addition, responses to a question asked of students at the end of the experience, in which they were asked to indicate their preferences for the characteristics of the hybrid laboratory, are analyzed. The results show that the flexibility and accessibility of the remote laboratory were positively valued. The implications of these findings for the design of hybrid laboratories and the teaching of digital electronics are discussed